2014
DOI: 10.1128/aem.04146-13
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of 4-Hydroxybutyrate to Acetyl Coenzyme A and Its Anapleurosis in the Metallosphaera sedula 3-Hydroxypropionate/4-Hydroxybutyrate Carbon Fixation Pathway

Abstract: The extremely thermoacidophilic archaeon Metallosphaera sedula (optimum growth temperature, 73°C, pH 2.0) grows chemolithoautotrophically on metal sulfides or molecular hydrogen by employing the 3-hydroxypropionate/4-hydroxybutyrate (3HP/ 4HB) carbon fixation cycle. This cycle adds two CO 2 molecules to acetyl coenzyme A (acetyl-CoA) to generate 4HB, which is then rearranged and cleaved to form two acetyl-CoA molecules. Previous metabolic flux analysis showed that two-thirds of central carbon precursor molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 41 publications
(42 reference statements)
1
27
0
Order By: Relevance
“…Third, the oxygen stability of 4-hydroxybutyryl-CoA dehydratase that until now has been assumed to require anoxic conditions because of its radical mechanism (33) is a prerequisite for the aerobic operation of the thaumarchaeal HP/HB cycle, lowering enzyme maintenance and turnover costs further. Interestingly, 4-hydroxybutyryl-CoA dehydratase from M. sedula also is robust in the presence of oxygen, as reported during revision of this work (34).…”
Section: Discussionsupporting
confidence: 58%
“…Third, the oxygen stability of 4-hydroxybutyryl-CoA dehydratase that until now has been assumed to require anoxic conditions because of its radical mechanism (33) is a prerequisite for the aerobic operation of the thaumarchaeal HP/HB cycle, lowering enzyme maintenance and turnover costs further. Interestingly, 4-hydroxybutyryl-CoA dehydratase from M. sedula also is robust in the presence of oxygen, as reported during revision of this work (34).…”
Section: Discussionsupporting
confidence: 58%
“…Third, it was shown that the 3HP/4HB cycle can drive rapid autotrophic growth with a doubling time of less than five hours (Hawkins et al, 2013), suggesting the potential for fast pathway kinetics. Components of the 3HP/4HB cycle can be identified in genomes within the crenarchaeal order Sulfolobales (Kockelkorn and Fuchs, 2009), and has been studied most intensively in the extremely thermoacidophilic archaeon Metallosphaera sedula (T opt = 73°C; pH opt = 2.0) (Auernik and Kelly, 2010; Berg et al, 2010; Hawkins et al, 2014). The cycle can be divided into three sub-pathways to track the reduction of CO 2 into acetyl-CoA.…”
Section: Introductionmentioning
confidence: 99%
“…All genes encoding the enzymes of the crenarchaeal HP/HB cycle were identified in M. sedula, and the corresponding proteins were biochemically characterized (19,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). In contrast, only four enzymes involved in the thaumarchaeal HP/HB cycle were biochemically characterized (13).…”
mentioning
confidence: 99%